Consequences of zinc deficiency in selected diseases - literature review - Płaczek, Alicja; Machaj, Dominik; Białas, Filip; Cyboran, Katarzyna; Kuc, Monika (Journal of Education, Health and Sport, 2022)
Zinc is one of the most important micronutrients. It is essential for maintaining health. It is supplied with food, therefore an appropriate diet is the basis for maintaining its appropriate level in the body. The cause of the deficiency may be insufficient supply or malabsorption. [2] Deficiency symptoms manifest themselves in the form of ailments from various systems. A relationship has been shown between zinc deficiency and the occurrence of certain diseases, e.g. cardiovascular diseases, diabetes and depression. Supplementation has a beneficial effect in the prevention and alleviation of the course of certain diseases. [1]